PENGGUNAAN WATER HEATING PADA MESIN PENGKONDISIAN UDARA SEBAGAI ALAT PENGENDALI KELEMBABAN UDARA DI DALAM RUANG OPERASI DI RUMAH SAKIT - Wardoyo, Wardoyo (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2015)
This research was aimed to observe the performance of water heating as an air moisture controller device in a hospital surgery room. The way the research was outside air in 27 degrees until 30 degrees celcius and moisture of 60 until 70 percent made suitable with requirement conditions determined for surgery room in the hospital i.e. 19 until 24 degrees celcius and moisture of 45 until 60 percent. To make that condition, the surgery room was equipped with air conditioner machine and water heating as an air moisture controller device. Hot water was circulated in water heating and air moisture was measured by a hygrometer. Out of this research it obtained: measuring moisture value higher than theoretic moisture value. Calorie volume in water heating increased with water volume that was constant so that water heating could control air moisture. There was a suitability in an air moisture ratio and calorie volume in water heating so that air moisture in surgery room could be measured as requirements.